"I totally didn't need to be there in person": New York women's preferences for telehealth consultations for sexual and reproductive healthcare in primary care. (19th September 2022) - Srinivasulu, Silpa; Manze, Meredith G; Jones, Heidi E
Abstract: Background: Expanding telehealth in the United States during the COVID-19 pandemic supported patients with needed sexual and reproductive healthcare (SRH) for continuity of care and reproductive autonomy. While telehealth for SRH is feasible and acceptable, studies have not explored patient preferences towards telehealth SRH from primary care settings. Objective: We explore New York women's preferences for telehealth SRH in primary care. Methods: In 2021, we conducted 5 focus groups and 8 interviews with New York women of reproductive age who had a consultation with a primary care provider in the last year as part of a larger study on assessing SRH quality in primary care. We queried on experiences with telehealth for SRH and perceptions of measuring SRH quality in primary care telehealth consultations. We employed reflexive thematic analysis. Results: We recruited 30 participants. They preferred telehealth for "basic" SRH conversations, such as contraceptive counselling, and desired in-person consultations for "complex" topics, like pregnancy and preconception, especially if nulliparous. Telehealth benefits included convenience, simplicity of some SRH needs, and alleviating power dynamics in patient–provider relationships. Challenges included lack of one-on-one connection, seriousness of pregnancy discussions, privacy, and internet access. Measuring quality of telehealth SRH should include fostering positive and engaging environments. Conclusion: Participants find telehealth SRH in primary care preferable, underscoring the importance of offering and expanding this care. As telehealth SRH expands, providers should strengthen quality by building rapport to facilitate conversations on "serious" topics and their ability to help patients remotely. Lay Summary: The expansion of phone- and video-based consultations in the United States for sexual and reproductive healthcare (SRH) during the COVID-19 pandemic supported patients with needed continuity of care, while minimizing virus exposure. As COVID-19 becomes endemic, medical organizations and providers recommend sustaining and expanding telehealth for SRH and other primary care needs. No studies to date have explored patient acceptability of telehealth for SRH services broadly in primary care settings. This brief report explores preferences for telehealth for SRH in primary care among New York women of reproductive age through focus groups and interviews. Overall, participants preferred telehealth for "basic" SRH conversations, such as contraceptive options, and in-person consultations for more "complex" topics, like pregnancy and preconception. Benefits of telehealth services included convenience, simplicity of some SRH needs, and being able to minimize uncomfortable power dynamics in the patient–provider relationship. Challenges included the lack of one-on-one connection with a provider, the perceived seriousness of pregnancy-related conversations, privacy, and internet access concerns. Patients find telehealth for SRH in primary care preferable, especially for simple SRH conversations, which suggests the importance of continuing to offer services in this manner.